ANALISIS SISTEM PENETAPAN PEMUNGUTAN DAN PENAGIHAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DI KABUPATEN MINAHASA - Wowiling, Christina; Nangoi, Grace B.; Affandi, Dhullo (Universitas Sam Ratulangi, 2018)
The purpose of this research is to analyze the adequacy of the system of stipulation, collection and collection of non-metal mineral and rock taxes in the Minahasa regency and whether they are in accordance with the applicable laws and regulations. The method used in this study is descriptive qualitative, namely analyzing the adequacy of the tax collection and collection system. At the Regional Tax and Retribution Management Agency (BPPRD), Minahasa Regency implemented a Non-Metal and Rock Mineral Tax collection system using the Self Assessment System where the taxpayer determines the amount of tax owed himself, this system has provisions for taxpayers to be active starting from counting, deposit and report the tax owed yourself. The results of the research show that the non-metal mineral and rock tax collection and collection system is running well and in accordance with the applicable laws and regulations. However, there are still inadequate internal control matters such as not using an application system that has been internally controlled and there are no rules related to integrity and ethical values.Keywords: Non-Metal Mineral and Metalliferous Mineral Tax Collection System, Non-Metallic Mineral and Stone Taxes